Analysis of lordosis and kyphosis in swimming - Höfling, I.; Linnenbecker, S.; Ungerechts, B.; Nicol, K. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION In the treatment of lower back pain backstroke swimming is frequently suggested as being particularly valuable whereas negative effects are ascribed to breaststroke swimming although there is no evidence in the literature, which supports the recommendation. Therefore the purpose of the present study was to analyse the spine during complete swimming cycles of different strokes in recreational swimmers. METHODS In 46 healthy subjects of three age groups (A: 13-14, B: 25-35, C > 50 years) the lumbar lordosis and thoracic kyphosis were compared in breaststroke (BR) and two different types of backstroke swimming (BK I: simultaneous pull, BK II: alternating pull) as well as the standing position (ST). Sequences of each stroke were recorded with an underwater video camera allowing a lateral view of the back profile. Afer digitalization and evaluation further calculations were carried out to describe the lordosis and kyphosis using two methods: one based on a radius- and the other on an angle-model. RESULTS There were no significant differences between the two types of backstroke swimming (BK I and II). The lordosis tended to be less in BK than in BR, however, the values did not always differ significantly in all groups and both methods. Compared to ST the mean and the minimum values of the swimming cycle were lower in BR and BK, the maximum values tended to be higher than in ST. The kyphosis was significantly less in BR than in BK and ST. The mean values of BK did not differ significantly from ST, while the minimum values in BK tended to be lower and the maximum values were significantly higher. DISCUSSION Potentially detrimenatal effects, which are sometimes ascribed to breaststroke swimming because of an increase of the lumbar lordosis, were not confirmed in this study. The results suggested no greater bending of the spine in breaststroke swimming compared to the standing position. In contrast to a common assumption there was no clear evidence that the lordosis is significantly less pronounced in backstroke than in breaststroke swimming. The thoracic kyphosis was less in breaststroke than backstroke swimming or standing. Consequently, backstroke swimming should not be considered as being far more suitable in the prevention and rehabilitation of low back pain patients than breaststroke swimming.